Determinación De Residuos De Plaguicidas Organoclorados Y Organofosforados En Leche Cruda En 2 Fincas Del Departamento Del Quindío (2014)
Milk is the main component of the diet, especially for vulnerable groups such as infants, school children and older adults. By their physicochemical characteristics, mainly lipid solubility, milk is a means of easy contamination by external agents such as chemical type gases emitted into the atmosphere, industrial waste, drug residues, mycotoxins , pesticide residues , among others. Some of the chemicals included in the above groups are resistant to degradation, persist in the environment and can be passed to cattle, accumulate in tissues and eliminated by the mammary glands. The toxicity of these compounds, affecting the health of humans causing alterations in lipid metabolism, transport of glucose and vitamins, some are considered mutagenic, teratogenic or carcinogenic. The aim of this work was the determination of residues of organochlorine and organophosphorus pesticides in raw milk on 2 farms Quindio. For this purpose 54 samples in water, cans, liners and milk were taken. For this analysis, the extraction method is used in solid phase SPE columns of florisil using as solvent and hexane. This technique was modified by preliminary tests were conducted to find the best instrumental conditions; we have obtained recoveries of 65-70 %. For the determination of these substances a gas chromatograph equipped GC-μECD/FID, injection port split / splitless mode and manual injection was used. Resulting in the water , cans and liners do not contain pesticides detected in milk and showed that on the farm 1, the two samplings carried out in August and September traces of endosulfan sulfate and methoxychlor were detected without But do not exceed the maximum allowable limits for these compounds . In farm 2 is not detected in any sample taken for the presence of pesticide residues.